Preliminary Study On Fabrication And Characterization Of Compatibility HA/TPU Composite Filament For Bone Scaffold - Mohd Ariff, Mohamad Fitri Azim (Universiti Sains Malaysia, 2022)
The objective of this research is to fabricate and characterize hydroxyapatite/ thermoplastic polyurethane (HA/TPU) composite filament. HA/TPU composite filament is a matrix of TPU polymer with addition of HA as bioceramic filler. The parameter investigated in this research is the different weight percentage of HA filler (10, 15 and 20 wt%) in HA/TPU filaments. Three composites of HA/TPU and one pure TPU reference material were fabricated. To evaluate the feasibility of HA/TPU composite filament to be used as filament in Fused Deposition Modelling (FDM) or 3D printing method, water Contact Angle (CA), Melt Flow Rate (MFR), Fourier Transform Infrared Spectroscopy, (FTIR) and Thermogravimetric Analysis (TGA) were used for characterization. CA results shows that, the wettability of HA/TPU with 20 wt% has the highest water contact angle value of roughly 67°. Meanwhile, there are no notable changes between the other two HA/TPU composite filaments and pure TPU filaments. MFR results show that pure TPU has considerably lower MFR value when compared to HA/TPU with 20 wt% of HA. FTIR analysis shows that the polymers shared four major peaks: the CH2 stretching vibration peak, the amide I band, the -NH stretching vibration peak, and the -NH stretching vibration peak (amide II band). TGA graph shows a weight retention percentage at high temperatures ranging from 300°C to 350°C for pure TPU and 250°C to 450°C for TPU with 20wt% HA.